Respuesta :
Answer:3
Step-by-step explanation:
you have to multipy 3 by each of th numbers in the ( ) and then sove by subtracting
3 x 2= 6 and 3 x -1 = -3 so 6-3= 3
Answer:
[tex]3(2 - 1) = 3[/tex]
Step-by-step explanation:
Use PEMDAS.
===================================
[tex]3(2-1)\\\rule{150}{0.5}\\\rightarrow 2 - 1 = 1\\\\3(1)\\\\3 \times 1\\\\\boxed{3}[/tex]
===================================
You can also distribute 3 into the parentheses and evaluate form there.
[tex]3(2-1)\\\rule{150}{0.5}\\\rightarrow 3 * 2 = 6\\\rightarrow 3 * -1 = -3\\\\3(2-1) \rightarrow \boxed{6 - 3}\\\\\boxed{3}[/tex]
===================================
Hope this helps!